Modeling carbon dynamics in teak plantations of Kerala - Manjunatha M (Department of tree physiology and breeding, College of forestry, 2015)
The study on “Modeling carbon dynamics in teak (Tectona grandis Linn. F) plantations of Kerala” was carried out in teak plantations of Kerala Forest Department during 2011-2015. The study attempted to estimate the carbon stocks in teak plantations and model the soil carbon using ‘Century’ soil carbon modelling tool. The modelling tool was used to analyze the soil carbon under different scenarios. The study also developed of a system dynamic model for carbon prediction for teak plantations. Teak plantations were divided into five strata based on age (0-5, 6-10, 11-20, 21-30 and >30 years). Thirty samples were selected at random for each stratum. Quadrants of 50 m x 50 m size were established in each sample for vegetation analysis. Fifty samples among the 150 samples so selected were used for the validation of the developed model. Ten plantations each from each age class (50 samples) were selected at random for soil studies. Pits of 1m x 1m x 1 m were dug in each sample plot and soils were collected at 0-20, 20-40, 40-60 and 60-100 cm depths. The total litter was collected from each plot at an interval of three months to estimate diurnal litter fall. Soil C, N, S was estimated along with the N, P, K and lignin of litter. Biomass of the study site was estimated using allometric equations. Secondary data on weather parameters were collected from appropriate sources. Significant differences were not observed among the different age classes and soil depths in case of sand and silt content of soil. However, clay content varied between the different age classes and soil depths. Although water holding capacity did not vary among the plantations of different age class in the surface layer (0-20 cm), it varied among the age classes at 20-40 cm. The bulk density did not differ between age classes, while it was higher in deeper layer of the soil (1.1 to 1.36 g/cm3). Soil pH was moderately acidic (5.1 to 6.0). The soil N varied from 0.07 to 0.34 % in plantations, while the values ranged from 0.43 to 1.23 % in natural forests. Nitrogen content was highest in the surface and decreased with the depth in both teak plantation and natural forest. The mean values of available P in the teak plantations and natural forest varied from 1.0 to 4.81 g/kg and 3.16 to 4.82 g/kg respectively. Significant differences in soil C was noticed between plantation and natural forest. While the soil C did not vary between various age classes, it was higher in surface layers compared to deeper layers. Simulation by CENTURY model in teak plantation indicated decline in total SOC up to 50 per cent by 30th year from the initial value of 6168 g C m-2. There after SOC pool declined at a slower rate till 45 years and reached 2702 g C m-2 by 80 years. There was rapid decrease in active carbon pool in teak plantations from 6.25 g C m-2 to 2.88 g C m-2 initially (up to 3rd year) and slow increase to 10.17 g C m-2 by 9th year. By the end of 80th year, the active pool almost doubled to 12 g C m-2. Slow carbon pool in teak plantations reduced from 3700 g C m-2 to 1224 g C m-2 by 22 years and reached 920 g C m-2 at an age of 80 years. Passive carbon pools in teak plantations more or less remained stable (2150.84 to 1912 g C m-2). Analysis indicated that the model was able to predict the values with high efficiency (0.922) and accuracy (R² = 0.9156) Fire reduced total SOC in teak plantation. The study found a 20 per cent decline in the total SOC by the 22nd year of plantation establishment. The SOC reached at 2343 g C m-2 at the age of 30 year of teak plantation compared to 2702 g C m-2 in a normal plantation. Teak plantation converted to natural forest resulted in an increase of SOC pools by 163 g C m-2 compared to that of the teak plantation. Conversion of teak plantation to agroforestry system resulted in marginal decline of 156 g C m-2 in SOC by 30 years. The SOC in teak plantation converted to ginger cultivation declined by 39 per cent at 30 years after ginger cultivation. Conversion of teak plantation to agriculture (pulses and tuber) resulted in significant reduction all the carbon pools. The SOC declined to 43 per cent at 30 years. A system dynamic model of soil carbon dynamics was developed using STELLA software. It was observed that the model was able to predict the total SOC with high precision (ME=0.69). The present study indicated that modelling is suitable for studying C dynamics in soils under teak plantations. Present results highlight the potential of using these tools for reliable evaluation the carbon sequestration potential of management interventions at plantation as well as landscape level.